Common tasks of teaching as a resource for measuring professional content knowledge internationally - Hoover, Mark; Mosvold, Reidar; Fauskanger, Janne (NOMAD Nordic Studies in Mathematics Education, 2014)
In the United States, extensive time and money has been invested in developing and validating measures of mathematical knowledge for teaching (MKT). Although studies of adaptation of these measures generally conclude that they are useable in other countries, cultural differences in teaching prompt questions about whether theories and measures of knowledge for teaching are culturally specific. This article argues that the issue turns on the meaning of ”teaching” and ”tasks of teaching” and it recommends increased efforts to identify professionally defensible mathematical tasks of teaching that can serve as a common foundation for conceptualizing and measuring mathematical knowledge for teaching internationally.